2008
DOI: 10.1128/jvi.01520-07
|View full text |Cite
|
Sign up to set email alerts
|

Akt Plays a Critical Role in Replication of Nonsegmented Negative-Stranded RNA Viruses

Abstract: The order Mononegavirales (comprised of nonsegmented negative-stranded RNA viruses or NNSVs) contains many important pathogens. Parainfluenza virus 5 (PIV5), formerly known as simian virus 5, is a prototypical paramyxovirus and encodes a V protein, which has a cysteine-rich C terminus that is conserved among all paramyxoviruses. The V protein of PIV5, like that of many other paramyxoviruses, plays an important role in regulating viral RNA synthesis. In this work, we show that V interacts with Akt, a serine/thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
77
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 62 publications
(64 reference statements)
6
77
2
2
Order By: Relevance
“…Conversely, overexpression of TIAR enhances SeVmediated apoptosis. Sun et al (32) reported that PI3K activity is needed for many steps of virus replication; it will be interesting to examine whether it is needed for trRNA synthesis as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, overexpression of TIAR enhances SeVmediated apoptosis. Sun et al (32) reported that PI3K activity is needed for many steps of virus replication; it will be interesting to examine whether it is needed for trRNA synthesis as well.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the NF-B pathway in this action remains controversial (26). Recently, it has been reported that Akt activity is also required for optimal replication of paramyxoviruses and other nonsegmented negative-strand viruses (32).…”
mentioning
confidence: 99%
“…Sun et al (53) recently reported that PIV5 V protein interacts with Akt, a serine/threonine kinase, and Akt plays a critical role in PIV5 replication. We have examined the interaction of the hPIV2 V and Akt.…”
Section: Discussionmentioning
confidence: 99%
“…AKT phosphorylates the P protein of PIV5 to upregulate its gene expression whereas PLK1's phosphorylation of P of PIV5 downregulates its gene expression. It has been proposed to target host kinases that are critical for viral RNA synthesis as an antiviral strategy for these paramyxoviruses (25). The identification of S/T residues and phosphorylation sites within MuV P will aid in the identification of host kinases that are important for MuV replication, which will lead to novel targets for anti-MuV drug development.…”
Section: Discussionmentioning
confidence: 99%